Komunikasi Antar Budaya pada Komunitas Aron di Berastagi - Barus, Remaja Putra; Barus, Rehia Karenina Isabella (Universitas Medan Area, 2019)
Researcher observing how the interculture communications patterns onaroncommunity in Berastagi .The purpose is to analyze the processes and pattern of communication that happened between various ethnics in aron community as well as the constraints that emerge in the interculture communication process in Berastagi.As many ethnics become aron, researcher focusing on the communications proccess between the Toba, Simalungun, Java, Nias, Karo, Gayo and Alas.A qualitative approach with the methods of communicationethnography was adopted in this research. Theresearch result indicates the intercultural communication on aron communities included in the interactive, transactional, dynamic and the limited interactive communication. In addition, the process of communication between intercultural ethnics also included into the primary and secondary communication pattern. Of all the intercultural communication process within the aron community, there are communication constraints such as prejudice and stereotype in the form of satire done by Karo to Toba.